OLIGO CHITOSAN TEST IN THE INITIAL BULBIL GROWTH OF ILES-ILES (Amorphophallus muelleri Blume) - Sumarwoto Sumarwoto; Sugeng Priyanto (Jurnal Agrivet, 2020)
Oligo chitosan is a supplement that can increase growth, accelerate flowering, and increase productivity in several types of agricultural crops, rice and horticultural commodities. The findings of this study, encourage the authors, to further test the Oligo chitosan on the initial growth of the bulbs of Iles-iles. It is known, that Iles-iles (Amorphophallus muelleri Blume) or "Porang" is one type of tuber whose life cycle is quite long, has a slow-growing bulbil, especially in the dry season. This growth delay is caused in addition to genetic traits, also dry environmental conditions come into effect, so if entering the rainy season at a certain time span will soon show a good appearance of growth. Bulbil as a planting material, in order to grow immediately, it is necessary to strive to accelerate its growth, one of which is to use Oligo chitosan. In the cultivation of iles-iles the use of Oligo chitosan to accelerate bulbil growth has never been done. Technological innovations produced by BATAN, have the opportunity to be used in the development of crop cultivation made from tubers. This study aims to test Oligo chitosan to encourage the realization of early growth of bulbil, through the treatment of immersion time and the concentration of Oligo chitosan which is higher than previous experiments that the authors have done. The experiment was conducted in the rainy season of 2019/2020 in the experimental farm of the UPN "Veteran" Yogyakarta Wedomartani Faculty of Agriculture under a tree stand, using a Split Plot Randomized Completely Block Design (RCBD) with three replications. As the main plot is the soaking time of Oligo chitosan solution, consisting of three kinds, namely 2.5 hours (L1), 5 hours (L2), and 7.5 Hours (L3), and as a sub plot is the concentration of the solution consists of 3 stages, namely (5.0 ‰ (K1), 10 ‰ (K2), and 15 ‰ (K3) and one control (without Oligo chitosan). The data obtained were analyzed by Variance Analysis with 95% confidence level, and for the difference test the Duncan Multiple Range Test (DMRT) was used at the 5% level and the Orthogonal Contrast Test The results showed that soaking Oligo chitosan for 2.5 hours (L1) was sufficient to provide a better initial growth effect for Ilesiles bulbil, with a fairly high concentration of 15 ‰ (K3).Keywords: Oligochitosan, Iles-iles or Porang, bulbil, soaking and concentration